PENGARUH PEMERIKSAAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Assa, Jeremiah Reinhart; Kalangi, Lintje; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
One of the largest state revenues comes from the tax sector. Tax receipts are a major source of financing and national development to improve people's welfare. One of the tax revenues is derived from Income Tax (PPh). Sanctions and tax audit is one of the factors that influence taxpayer compliance. This study aims to determine the effect of sanctions and tax audits on taxpayer compliance in paying taxes. This research uses quantitative research method. The results showed that tax audit and sanctions have a significant effect on taxpayer compliance in paying taxes. This is a reference so that supervision in the form of inspection can be maximized so as to improve taxpayer compliance in paying taxes.Keywords: tax audit, tax sanctions, tax compliance